Facts and Features of Human Language in Social Media: Interaction and Culture of Alpha Generation - Sari, Rahma; Lubis, Aulia Khairunisa; Daulay, Sholihatul Hamidah (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
This study investigates the role of speech and language in shaping the communication of ideas and emotions on social media, with a particular focus on TikTok. Social media platforms, while enabling widespread and instantaneous interaction, often have both positive and negative consequences for individual users and targeted groups. By employing a qualitative methodology, this research explores how language choices on TikTok influence personal expression, identity construction, and collective social dynamics. Analyzing the linguistic behaviors of 10 TikTok users, the study identifies how multimodal elements such as emojis, memes, and audio-visual integrations enhance digital communication. The findings reveal that the informal, rapid nature of social media communication reflects broader societal trends toward dynamic and hybrid linguistic forms. Furthermore, social media serves as a space for fostering cultural diversity, promoting social movements, and enabling users to create and refine their online personas. However, the study also highlights the challenges posed by such digital communication, including the potential for misunderstandings and the reinforcement of social inequalities. By situating these findings within the context of evolving digital communication, this research offers valuable insights into the interplay between language, identity, and culture in the digital age. It contributes to broader discussions about the implications of multimodal communication for literacy, linguistic evolution, and social interaction in a rapidly globalizing world.Keywords: Multimodal Language, TikTok, Social Media